Pengaruh Serbuk Abu Cangkang Kerang Sebagai Bahan Pengganti Filler Pada Campuran Aspal - Kartika Indah Sari (JOURNAL OF CIVIL ENGINEERING BUILDING AND TRANSPORTATION, 2021)
Asphalt is the main ingredient in road pavement. The specification of the Asphalt Concrete Wearing Course (AC-WC) mixture refers to the Specifications of the Ministry of Public Works, Directorate General of Highways 2010 revision 1 (BM 2010). Marshall test includes: stability, flow, Marshall Quotient, Voids In Mixture (VIM), Voids in Mineral Aggregate (VMA), and Voids Filled by Asphalt (VFA). In the AC-WC mixture that uses fine aggregate, namely clam shell filler. The shells used are from the Tanjung Balai area. From the results of the study, the effect of partial replacement of oyster shell filler was 15% and 25% which showed a change in the stability value for 15% mixture of 1192 kg and 25% of 1245 kg while the Specifications of the Ministry of Public Works of the Directorate General of Highways 2010 revision 1 of 800 kg had met specification requirements.